Alterations in scapulothoracic and humerothoracic kinematics during the tennis serve in adolescent players with a history of shoulder problems - Gillet, B.; Begon, M.; Diger, M.; Berger-Vachon, C.; Rogowski, I. (Sports Biomechanics, 2021)
The tennis serve generates high musculoskeletal loads at the shoulder complex, making athletes particularly vulnerable to chronic injuries, especially adolescent players. Chronic injuries are commonly related to altered scapular kinematics. This study explored the effects of a history of shoulder problems involving humerothoracic and scapulothoracic kinematics during the tennis serve at low speed in adolescent competitive players with and without a history of dominant shoulder problems. Totally, 28 adolescent tennis players were split into two groups, those with and those without a history of shoulder problems. Data on humeral and scapular kinematics relative to the thorax were collected using an electromagnetic system during slow velocity serves. The two groups`s humerothoracic and scapulothoracic 3D joint angles were compared both at the end of the cocking phase and at the end of the acceleration phase of the tennis serve. At the end of the cocking phase, the players with a 30 history of shoulder problems showed less humeral abduction and external rotation and more scapular upward rotation. This group also showed less humeral abduction at the end of the acceleration phase. Players with a history of shoulder problems adapted their humerothoracic and scapulothoracic orientations to preserve shoulder integrity during the tennis serve.